Identifying the moderating effect of trust on the adoption of cloud‐based services. (3rd January 2017) - Rahi, Shiromani Balmukund; Bisui, Sandip; Misra, Subhas Chandra
Summary: Cloud computing provides a way to coordinate and share relevant information and data on real‐time basis over an organization. The adoption of cloud services is one of the most emerging technological advances in the practice of current competitive business environment. The research done in this article is based on the analysis of the data obtained from the semiconductor sector. Cloud adoption would most likely be the best answer for them. However, because of various types of complexities, semiconductor industries may have to confront with a few trust issues while receiving cloud services. This article aims to identify the trust factors in the adoption of cloud services in semiconductor industries. Further, the moderating effect of these trust elements related to the technological, organizational, and environmental success factors has been discussed here. On the basis of literature survey, a hypothetical model has been developed, and the relationships among the latent variables have been studied by using structural equations. The study reveals that while trust factors moderate the technology and environment‐related success factors, there is not much moderating effect of the trust issues on the organization‐related success factors in the adoption of cloud services in semiconductor industries. Abstract : KEY FINDINGS: The research done in this article is based on the analysis of the data obtained from the semiconductor sector. The study reveals that trust factors moderate the technology and environment‐related success factors; there is not much moderating effect of the trust issues on the organization‐related success factors in the adoption of cloud services in semiconductor industries.